2004
DOI: 10.1002/er.986
|View full text |Cite
|
Sign up to set email alerts
|

A shock tube study of pyrolysis of tetrahydrothiophene at elevated temperatures

Abstract: SUMMARYA single pulse shock tube has been used to study the pyrolysis of a hydrogenated sulphur compound, tetrahydrothiophene over the temperature range 1686-1885 K and pressures between 2.4 and 3.5 bars. Product yield and composition was determined using capillary column gas-chromatography with flame ionization detection and flame photometric sulphur selective detection. The principal hydrocarbon products at all temperatures were C 2 H 4 and C 2 H 2 . Other hydrocarbon reaction products were CH 4 , C 2 H 6 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These two compounds have been used in wet chemical methods and in methods that involve pyrolysis for the production of metal sulfide NPs. The main sulfur decomposition products of tetrahydrothiophene are CS 2 , H 2 S, and thiophene [135] . On the other hand, the main sulfur decomposition products of thiophene are CS 2 , H 2 S, and elemental sulfur [136] .…”
Section: Decomposition and Gas‐phase Interactionsmentioning
confidence: 99%
“…These two compounds have been used in wet chemical methods and in methods that involve pyrolysis for the production of metal sulfide NPs. The main sulfur decomposition products of tetrahydrothiophene are CS 2 , H 2 S, and thiophene [135] . On the other hand, the main sulfur decomposition products of thiophene are CS 2 , H 2 S, and elemental sulfur [136] .…”
Section: Decomposition and Gas‐phase Interactionsmentioning
confidence: 99%
“…Various studiesPrevious studies have suggested the emergence of H 2 S as a major gaseous product during pyrolysis of thiophene above 1000 K [10]. It follows that, an atomic-base understanding of the decomposition of thiophenic compounds would be instrumental in the effort to reduce emission of sulfur species from accidental fires of coal.…”
Section: Introductionmentioning
confidence: 99%
“…The conversions of dibenzothiophene were also researched in the closed pyrolysis system by Dartiguelongue et al 9 recently, and they suggested the thermal-cracking mechanisms including the C-S bond cleavage leading to the degradation of the molecular skeleton and oligomerization of two dibenzothiophenes or dibenzothiophene with other aromatics produced in the process. Memon et al 10 reported the pyrolysis of tetrahydrothiophene in a shock tube in 2004 and found that hydrogen sulfide, carbon disulfide, thiophene, and ethyl mercaptan were the sulfurcontaining compounds produced. Clark et al 11 studied the hydrolysis and thermolysis of tetrahydrothiophene in relation to steam-stimulation processes and found that hydrogen sulfide is the main sulfur-containing compound.…”
Section: Introductionmentioning
confidence: 99%